Предмет: Алгебра,
автор: lodandelions
(а-7)²-2(а-7)(а+7)+(а+3)²
при: а=0,25
Ответы
Автор ответа:
0
(a - 7)² -2(a - 7)(a + 7) + (a + 3)² = a² - 14a + 49 -2(a² - 49) + a²+6a + 9 =
= a² - 14a + 49 - 2a² + 98 + a² + 6a + 9 = -8a +156 = 156 - 8a
при a = 0,25
156 - 8*0.25 = 156 - 2 = 154
= a² - 14a + 49 - 2a² + 98 + a² + 6a + 9 = -8a +156 = 156 - 8a
при a = 0,25
156 - 8*0.25 = 156 - 2 = 154
Похожие вопросы
Предмет: Литература,
автор: lilaradko4
Предмет: Английский язык,
автор: Tijcfujv
Предмет: Обществознание,
автор: artem142522052626
Предмет: Физика,
автор: berezkabelaya
Предмет: Геометрия,
автор: superlionleva1